The Cenozoic Multiple-Stage Uplift of the Qiangtang Terrane, Tibetan Plateau - Zhao, Zhongbao; Lu, Haijian; Wang, Shiguang; Li, Haibing; Li, Chao; Liu, Dongliang; Pan, Jiawei; Zheng, Yong; Bai, Minkun (Frontiers in Earth Science, 2022)
Cenozoic collision between the Indian and Asian continents is generally considered as the main driver forming the high Tibetan Plateau (TP). However, it remains hotly debated when and how the relatively flat and highly elevated TP was formed. Here, we present combined analyses of the apatite fission track (AFT) and apatite (U-Th)/He (AHe) of 18 granite samples along three steep topographic transects in the central part of the Qiangtang Terrane (QT), TP. The results indicate that the AFT ages of all samples are mostly between 130 Ma and 80 Ma, while the AHe ages range from 80 Ma to 40 Ma. Further thermal history modeling indicates that no significant cooling occurred after 40 Ma for most samples, except those lying close to the Reganpei Co extensional fault in the QT. The results are generally consistent with other low-temperature thermochronogical data, as well as structural and sedimentologic data from the QT, suggesting that low relief and the relatively flat topography of the QT were almost completely formed before ~40 Ma. As increasing paleontological evidence, both megafossils and pollen had undergone a sharply changes from subtropical- to psychro-species, indicates a relatively low elevation (~2 km) at ~40 Ma and >2 km uplift during the Oligocene. We use simple one-dimensional isostatic modeling to assess the contribution of convective removal of the lithospheric mantle to the present elevation of the QT. The results suggest that a combined effect of isostatic rebound (≥2 km) and thermal expansion related to asthenosphere upwelling and subsequent crustal base heating (~0.4 km) led to the final uplift of the QT. Therefore, the QT experienced multiple-stage uplift processes which were controlled by crustal thickening before ~40 Ma and lithospheric mantle delamination during the Oligocene, respectively.